CB2E through CCB and OCB (A marketing golden triangle for new era) - Nezakati, Hossein *; Asgari, Omid (2010)
This research attempts to propose a concept in Marketing New Era to present an approach (Golden Triangle) for achieving customer based brand equity (CBBE) through customer citizenship behavior (CCB) and organizational citizenship behavior (OCB) with human resource empowerment (HRE) in Age of Participation (AOP). The 11 stage Procedure for building this conceptual model is considered as: 1) preparation of individuals and management; 2) requirements for empowerment process and utilization of three international aspect of empowerment : National, Culture, Values; 3) three dimensions of HRE process and their symbolic aspects;4)HRE emergence; 5) OCB dimensions in their innate forms and their enforcement during these procedures; 6) instrumental factors in creating OCB and outcome of HRE in one procedure; 7) OCB symbolism and reach employee empowerment; 8) consequences of OCB and use them for reach to creating factors of CCB; 9) Creating factors of CCB and overlapping with consequences of OCB;10)CCB emergence and contextual factors of CCB and finally 11)reach to CBBE. The results of this study showed that eight factors out of eleven (73 percents of factors) that make up OCB and consequences of HRE and also fifteen factors out of eighteen (83 percent of factors) that make up CCB and consequences of OCB are analogous indicating the fundamental relationship of HRE with OCB and OCB with CCB and CCB with CBBE.